NUMERICAL INVESTIGATION OF DEPTH RATIO EFFECTS ON THERMOHYDRAULIC PERFORMANCE OF A HEAT EXCHANGER WITH V-CUT TWISTED TAPE - Farrel Rizqiadinata; Damora Rhakasywi; Nicky Yongkimandalan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Using Computational Fluid Dynamics (CFD), this research evaluates the thermo-hydraulic effects of altering the depth ratio of V-cut twisted tape (VTT) inserts within tubular heat exchangers. Three specific configurations (De/w = 0.25, 0.35, and 0.45) were simulated and compared to baseline cases of plain tubes and traditional twisted tapes. System characteristics were analyzed using flow behavior, Nusselt number, friction factor, and the Performance Evaluation Criterion (PEC). To ensure reliability, the numerical framework was verified using established empirical correlations and experimental data, yielding deviations below 5%. The simulated outcomes indicate that swirl generation, enhanced radial mixing, and thermal boundary-layer disruption drive the heat transfer improvements of the twisted tapes, with the V-cut geometries accelerating vortex generation and fluid recirculation. Although VTT systems successfully optimize thermal dissipation, they incur elevated hydraulic penalties. This trade-off between pressure drop and thermal efficiency is clearly reflected in the PEC trends, where flow visualizations confirm that larger depth ratios significantly augment fluid mixing and thermal restructuring.